Health Promoters & Factors Influencing the Performance of Health Promoters: Literature Review - Dewi Wulandari; Antono Surjoputro; Syamsulhuda Budi Mustofa (International Journal Labs, 2022)
Indonesia experiences a double burden of disease. According to Riskedas 2018, non-communicable diseases have increased and the Gerakan masyarakat hidup sehat (Germas) indicators have not been achieved. Health Promoters are health workers who play a role in the achievement of the Gemas indicator. For this reason, it is necessary to study the profession of Health Promoters and the factors that affect the performance of Health Promoters. The purpose of writing this literature review was to describe health promoters and analyze the determinants of the performance of health promoters. The method used is a literature review from journals and references related to Health Promoter, Health Promoter Performance and Performance. Health Promoters as registered health workers in carrying out their duties based on existing professional standards. There are 3 (three) national journals and 3 (three) international journals related to the performance of Health Promoters, from these three sources it is known that the performance of Health Promoters were influenced by capabilities, incentives and organizational support. Factors that affect the performance of Health Promoters are capabilities, incentives and organizational support, for that it is necessary to improve the performance of Health Promoters through increased capabilities, incentives and organizational support.